Experimental infection of cats with Cystoisospora felis - Andrea V. Scorza; Phyllis Tyrrell; Sara A. Jablonski Wennogle; Ramaswamy Chandrashekar; Michael R. Lappin (Journal of Veterinary Internal Medicine, 2021)
Abstract Background Cystoisospora felis is a common parasite of cats and is diagnosed by fecal flotation, but false‐negative results can be common. Hypothesis/Objectives To experimentally inoculate cats with C. felis oocysts, to compare fecal flotation and polymerase chain reaction (PCR) results, and to describe any clinical signs consistent with infection. Animals Six cats. Methods Cystoisospora felis oocysts were identified morphologically from feces of a naturally infected kitten with diarrhea, sporulated oocysts (5000) were inoculated to 6 cats that were negative for fecal parasites by fecal flotation and by a fluorescent antibody assay (FA) for Giardia spp. and Cryptosporidium spp. Cats were observed daily for the presence of clinical signs consistent with infection. Fecal samples were evaluated by fecal flotation and FA up to 3 times per week post inoculation (PI) to Day 27. Thirty‐six samples collected before inoculation and from Days 8, 10, 13, 15, and 20 PI were assayed using an internal transcribed spacer 1 (ITS1) PCR that amplifies DNA of C. felis. Results All cats were negative for C. felis by both assays before inoculation. All cats shed C. felis oocysts by Day 10 PI, oocysts were not detected by fecal flotation after Day 15 PI. Cystoisospora felis DNA was amplified from 24/36 (66.6%) fecal samples from 6/6 (100%) of the cats. Oocysts were not detected by fecal flotation in 4 of the samples that were positive for C. felis DNA by PCR. Clinical signs were not recognized in any of the study cats. Conclusions and Clinical Importance Fecal flotation is a convenient assay for detection of C. felis but could occasionally give false‐negative results when compared to this ITS1 PCR.